ESTABLISHING OF THE CONDITIONS OF THE BLEND OF PULP WITH BANANA (Musa paradisiaca L.) TO SUBMIT SPRAY DRYNG - LOPEZ M., Beatriz E.; CARVAJAL de P., Luz M.; MILLAN C., Leonidas de J. (Vitae, 2009)
Spray-drying is one of the methods used to dehydrate foods and prolong their life. This study aims to determine the optimum amounts of maltodextrin and rubber acacia to maximize ºBrix and minimize the viscosity in banana pulp for later spray drying. The maltodextrin has a significant effect for both, the content ºBrix as viscosity, but the latter also affects the interaction between maltodextrin and rubber acacia. It is necessary to find a balance between the maximum ºBrix and minimum viscosity for the drying process. Low viscosity allows a better flow of the mixture in the spray system (disk or diffusion) and a high concentration of solids totals increases the performance of the final product. The combination of treatments generating the better answer is above 39.95 g maltodextrin with 3.29 g rubber acacia. This combination of treatments is the point where ºBrix are maximum and viscosity is minimum, finding a value of 46.44 º Brix and 634.59 cP respectively.